Labor augmentation with oxytocin in low- and lower-middle-income countries: a systematic review and meta-analysisAJOG Global Reports at a Glance - Monica Lauridsen Kujabi, MD; Emmeli Mikkelsen, MD; Natasha Housseine, MD, PhD; Josephine Obel, MD; Brenda Sequeira D'Mello, MD; Dan W. Meyrowitsch, PhD; Kidanto Hussein, MD, PhD; Jeppe Bennekou Schroll, MD, PhD; Flemming Konradsen, PhD; Jos van Roosmalen, MD, PhD; Thomas van den Akker, MD, PhD; Nanna Maaløe, MD, PhD (Elsevier, 2022)
OBJECTIVE: Despite its worldwide use, reviews of oxytocin for labor augmentation include mainly studies from high-income countries. Meanwhile, oxytocin is a potentially harmful medication and risks may be higher in low-resource settings. We conducted a systematic review and meta-analysis of practices, benefits, and risks of oxytocin for labor augmentation in low- and lower-middle-income countries. DATA SOURCES: PubMed, Embase, PsycINFO, Index Medicus, Cochrane, and Google Scholar were searched for publications until January 1, 2022. STUDY ELIGIBILITY CRITERIA: All studies evaluating oxytocin augmentation rates were included. To investigate benefits and risks, randomized and quasi-randomized trials comparing oxytocin augmentation with placebo or no oxytocin were included. To explore risks more broadly, cohort and case-control studies were also included. METHODS: Data were extracted and quality-assessed by 2 researchers using a modified Newcastle-Ottawa scale. Generic inverse variance outcome and a random-effects model were used. Adjusted or crude effect measures with 95% confidence intervals were used. RESULTS: In total, 42 studies were included, presenting data from 885 health facilities in 25 low- and lower-middle-income countries (124,643 women). Rates of oxytocin for labor augmentation varied from 0.7% to 97.0%, exceeding 30% in 14 countries. Four studies investigated timing of oxytocin for augmentation and found that 89.5% (2745) of labors augmented with oxytocin did not cross the partograph's action line. Four cohort and 7 case-control studies assessed perinatal outcomes. Meta-analysis revealed that oxytocin was associated with: stillbirth and day-1 neonatal mortality (relative risk, 1.45; 95% confidence interval, 1.02-2.06; N=84,077; 6 studies); low Apgar score (relative risk, 1.54; 95% confidence interval, 1.21-1.96; N=80,157; 4 studies); neonatal resuscitation (relative risk, 2.69; 95% confidence interval, 1.87-3.88; N=86,750; 3 studies); and neonatal encephalopathy (relative risk, 2.90; 95% confidence interval, 1.87-4.49; N=1383; 2 studies). No studies assessed effects on cesarean birth rate and uterine rupture. CONCLUSION: This review discloses a concerning level of oxytocin use, including in labors that often did not fulfill criteria for dystocia. Although this finding is limited by confounding by indication, oxytocin seems associated with increased perinatal risks, which are likely mediated by inadequate fetal monitoring. We call for cautious use on clear indications and robust implementation research to support evidence-based guidelines for labor augmentation, particularly in low-resource settings.